Assessment of lumbosacral kyphosis in spondylolisthesis: a computer-assisted reliability study of six measurement techniques. - Glavas P; Mac-Thiong JM; Parent S; de Guise JA; Labelle H; Glavas, Panagiotis; Mac-Thiong, Jean-Marc; Parent, Stefan; de Guise, Jacques A; Labelle, Hubert (European Spine Journal, 2009)
Although recognized as an important aspect in the management of spondylolisthesis, there is no consensus on the most reliable and optimal measure of lumbosacral kyphosis (LSK). Using a custom computer software, four raters evaluated 60 standing lateral radiographs of the lumbosacral spine during two sessions at a 1-week interval. The sample size consisted of 20 normal, 20 low and 20 high grade spondylolisthetic subjects. Six parameters were included for analysis: Boxall's slip angle, Dubousset's lumbosacral angle (LSA), the Spinal Deformity Study Group's (SDSG) LSA, dysplastic SDSG LSA, sagittal rotation (SR), kyphotic Cobb angle (k-Cobb). Intra- and inter-rater reliability for all parameters was assessed using intra-class correlation coefficients (ICC). Correlations between parameters and slip percentage were evaluated with Pearson coefficients. The intra-rater ICC's for all the parameters ranged between 0.81 and 0.97 and the inter-rater ICC's were between 0.74 and 0.98. All parameters except sagittal rotation showed a medium to large correlation with slip percentage. Dubousset's LSA and the k-Cobb showed the largest correlations (r= -0.78 and r= -0.50, respectively). SR was associated with the weakest correlation (r= -0.10). All other parameters had medium correlations with percent slip (r= 0.31-0.43). All measurement techniques provided excellent inter- and intra-rater reliability. Dubousset's LSA showed the strongest correlation with slip grade. This parameter can be used in the clinical setting with PACS software capabilities to assess LSK. A computer-assisted technique is recommended in order to increase the reliability of the measurement of LSK in spondylolisthesis.